Preliminary Study of Blue Dye Removal on Small Sodium Alginate Hydrogel Beads in Fixed-Bed Glass Columns: A Basic Experimental and Mathematical Approach - Fuerte Aguilar, Ana Pamela; Cerrito Florencio, Brian Carlos; Zárate Castrejón, José Luis; Peña Caballero, Vicente (JÓVENES EN LA CIENCIA, 2025)
Bioadsorption within a packed-bed column is a bioprocess in which a continuous mass transfer occurs between two phases. In this preliminary study, the Bohart and Adams’ model considering bed depth, and influent dye concentration was studied to exhibit adsorption process of blue dye in glass columns. The dynamic bed capacity and the adsorption rate constant values are determined using the Bohart and Adams’ bed depth service model. Adsorption breakthrough curves were calculated as a function of C/C₀ vs time. Results showed that with the increases of bed height, and the decreases of influent dye concentrations, the breakthrough time was very similar for the four bed heights. The results demonstrated that SSAHB can be suggested as an adsorbent for removal of blue dye from wastewaters of industrial plants for the tertiary treatment of real liquid effluents,